Determination of antimony in bottled water in Polyethylene Terephthalate (PET) containers of ambulatory sale - Apesteguia, José A. (2018)
In Lima during the summer months, ambulatory sales do not meet quality standards for the sale of bottled water. A recent study by Shotyk et al, reported elevated levels of antimony in potable water stored in polyethylene terephthalate (PET) containers1 For this reason, the concentration of antimony in bottled water was studied in three samples during the months of February and March of 2013 of ambulatory sale on Alfonso Ugarte and Nicolás de Piérola avenues of metropolitan Lima in relation to the environmental temperature of sampling and the time of packaging. It was found that the average concentration of antimony on Alfonso Ugarte avenue was 1610 ng/L, The average concentration of antimony on Nicolás de Piérola avenue was 1600 ng/L. The antimony concentration of the samples of bottled water of ambulatory sale on Alfonso Ugarte and Nicolás de Piérola avenues was less than the máximum allowable value (20000 ng/L - WHO). The highest average concentration of antimony on Alfonso Ugarte avenue (2440 ng/L) and in Nicolás de Pierola avenue (2260 ng/L) are both in the third sampling (march 17, 2013). There is moderate correlation (0,426) of the concentrations of antimony and environmental temperature sampled on march 7th, on Nicolás de Piérola avenue. There is moderate (0,48) correlation of antimony concentrations and packing time sampled on February 17, on Alfonso Ugarte Avenue.